Cosmology and Logic in the Dao of Changes - Ma, Baoshan, 1942- (Book collections on Project MUSE., 2019)
The Book of Changes (Yijing, also known as I Ching) is generally recognized as the oldest among the ancient Chinese classics, tracing back to the yin-yang symbolic system that, according to traditional mythology, was created by the legendary Fu Xi (mid-29th century BCE). The Yijing's mystical origins and the dynamic nature of its image-numbers-the various diagrams, trigrams, and hexagrams-gave rise to subsequent interpretations by sages over millennia, along with differences in understanding. Ever since the Han dynasty (206 BCE-220 CE), there have been debates between two schools of thought: the image-number school, which focuses on the symbols as a means to divination; and the philosophy school, which values the work for its cosmological and ontological insights. Assimilating ideas from both schools, Ma Baoshan reestablishes the logical image-number system and reaffirms that this image-number logic is the foundation for understanding the Book of Changes in the context of contemporary research. As Ma explains in his introduction, "the aim of Cosmology and Logic in the Dao of Changes is not to study the image-number logic itself, but to discover the symbolic system inherent in the Book of Changes, and the image-number logic behind this system." His interpretations of the moving numbers and images: the Taiji, Hetu, and Luo-shu Diagrams, the Pre-heavens and Post-heavens Trigrams, as well as the 64 hexagrams, is always in the context of the continuity of mind and events. He renders this ontological existence as five onto-generative-beings (benti), which is a pioneering theory in the hermeneutical history of the Book of Changes. His theory is crucial in reminding researchers of this classic that without understanding its image-number foundation, it is impossible for anyone to comprehend it as a properly philosophical work.